Meeting Report of 10th National Emergency Medicine Congress & 1st Intercontinental Emergency Medicine Congress - Dundar, Zerrin Defne; Ergin, Mehmet; Karamercan, Mehmet Akif; Satar, Salim; Girisgin, Abdullah Sadik; Yildiz, Mustafa; Cander, Basar (Aves, 2014)
The 10th National Emergency Medicine Congress and the 1st Intercontinental Emergency Medicine Congress were held at Gloria Golf Resort Hotel Congress Center (Antalya, TURKEY) simultaneously between May 15 and 18, 2014. Due to the mining accident in the Soma Coal Mines prior to the congress, the social events were cancelled, and the congresses proceeded with the scientific program. Apart from the National Emergency Medicine Congresses, the EPAT had organized the International Symposium on Emergency Medicine and International Critical Care and Emergency Medicine Congress as part of its mission to get actively involved in the international emergency medicine arena. The Intercontinental Emergency Medicine Congress can be seen as the third link of this chain.
Keywords: Congress; emergency medicine; EPAT